Drying onions in Mali - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Onions are the most important cash crop for farmers of the Dogon Plateau. Of the total grown only 1% are consumed by the growers themselves. The harvest period lasts from early December to the end of April and peaks at the end of February. During...